Construction of bone marrow mesenchymal cells-derived engineered hepatic tissue and its therapeutic effect in rats with 90% subtotal hepatectomy - Yu, J.; Yuan, J.; Xu, R. (Cellular and Molecular Biology, 2014)
Engineered hepatic tissue (EHT) is considered as a promising strategy for healing acute liver failure (ALF), therefore, in the present study we evaluated the therapeutic potential of the EHT which engaged with bone marrow mesenchymal cells (BMSCs) derived hepatocytes (BMSCs-Hepas) in ALF rats. After characterization of isolated BMSCs, we seeded passage 3 BMSCs which have being cultured in medium containing 20 ng/ml hepatocyte growth factor (HGF) and 10 ng/ml epidermal growth factor (EGF) for 14 days on three scaffolds individually in Transwell system, and then cultured for more than 3 days to construct three kinds of EHT named EHT1, EHT2, and EHT3. Based on morphology and urea production assays, we chose an optimal one and transplanted it into ALF rat with 90% subtotal hepatectomy and assessed its therapeutic potential by survival time, hepatic encephalopathy score (HES) and related liver function test. The remnant liver was acquired, sectioned and identified by con-focal scanning microscopy. The isolated cells possessed basic properties of BMSCs, when cultured in hepatogenic medium for 2 weeks, BMSCs would restore to the functional properties of primary rats’ hepatocytes, expressing albumin (ALB) and alpha fetoprotein (AFP) simultaneously. Transplantation of EHT3 significantly prolonged the survival time, increased HES, and ameliorated the liver function. BMSC will be a newly cell source for the construction of EHT. Importantly, the EHT transplantation may be an effective strategy to treat ALF in clinic.